EXPLORING THE ENERGY PERFORMANCE OF WOOD CHIPS FROM SALIX VIMINALIS – KLON TORDIS (Innovation in Woodworking Industry and Engineering design, 2026)
The article presents the methodology and results of an experimental testing of the calorific value and ash content of wood chips, used as a fuel for heating and electricity plants. The wood chips was extracted from willows’ short rotation plantation of Salix Viminalis – klon Tordis. Studies were conducted in the “Department of Forest Harvesting, Logistic and Amelioration” of the Technical University in Zvolen, R of Slovakia. Wood chips produced from Salix Viminalis, klon Tordis indicates a high gross (20,597 MJ.kg-1) and net calorific value of dry mass (19,255 MJ.kg-1) under the specific production conditions. Naturally dried wood has a relative humidity Wr = 11,3 % and according to ISO 1928:2011 it has a clean net calorific value 16,907 MJ.kg-1. This gives grounds to assume that the wood produced from such an energy plantation will have high energy characteristics and will satisfy the market for energy chips.